Exploring the characteristics of gut microbiota in the development and progression of early-stage colorectal cancer based on metagenomic sequencing - Chen, Qianqian; Guan, Jing; Yang, Lu; Lv, Jie; Gui, Gen; Xu, Jianhua; Yang, Zhaoyun; Wang, Xu; Sun, Bin (Frontiers in Microbiology, 2025)
IntroductionColorectal cancer (CRC), a leading cause of cancer-related morbidity and mortality worldwide, often presents asymptomatically, resulting in late diagnosis. Accumulating evidence links gut microbiota dysbiosis to CRC initiation and progression.ObjectiveThis study aimed to investigate the differences in gut microbiota composition and diversity among healthy controls (HC) and patients with colorectal lesions—including common colorectal polyps, small colorectal adenomas (SCRA), large colorectal adenomas (LCRA), and intramucosal carcinoma (IMC)—to identify bacterial species associated with disease progression and provide novel insights into the diagnosis and treatment of CRC based on the “polyp-adenoma-carcinoma” sequence.MethodsA total of 250 participants were recruited from the First Affiliated Hospital of Anhui Medical University between July 2023 and June 2024. The cohort included 30 HC, 52 with common colorectal polyps, 58 with SCRA, 56 with LCRA, and 54 with IMC. Fecal samples were collected for bacterial DNA extraction, followed by metagenomic sequencing to analyze microbial diversity. Differential microbiota analysis was performed using the R package microbiomeMarker and LEfSe. Group classification and feature identification were conducted using a random forest model. Functional profiling was performed using DIAMOND against the KEGG and MetaCyc databases.ResultsNo significant differences in α-diversity were observed across the groups. β-diversity analysis revealed significant differences in Bray-Curtis and Jaccard distances among the groups. The composition and abundance of gut microbiota at the phylum, class, order, family, genus, and species levels were significantly altered. LEfSe analysis identified specific bacterial species with significant differences in IMC compared to other groups. Furthermore, the random forest model effectively distinguished patients with IMC from other groups based on distinct microbial signatures. Functional profiling revealed that the gut microbiota undergoes metabolic reprogramming from a homeostatic to a pro-tumorigenic phenotype during CRC progression as well as reduced protective pathway abundance and impaired energy/biosynthetic metabolism in CRC-associated microbiota.ConclusionGut microbiota profiles varied significantly among HC, polyp, SCRA, LCRA, and IMC groups. Specific microbial signatures were able to effectively differentiate IMC from both HC and non-malignant colorectal lesions, highlighting their potential as diagnostic biomarkers.